Behind Closed Doors: An Extensive Analysis of Trafficking with Human Beings in Kosovo (2020-2023) - Daci, Greta (Acta Universitatis Danubius. Juridica, 2024)
This research analyses human trafficking networks in Kosovo from 2020 to 2023, focusing on the current challenges. The objective is to uncover the patterns of operation of traffickers and identify the patterns of vulnerability among victims. The research is necessary as human trafficking continues to pose a significant challenge for Kosovo. The study builds on previous research regarding transnational organised crime and human trafficking in the Balkans. It compares the prior analysis of human trafficking. Expanding current research explores governance, socio-economic situation, and legal framework. Employing a mixed-method approach, analysing police annual reports, concluding interviews with law enforcement officials, statistical data, and analysis on recruiting patterns. The findings reveal the rise of human trafficking, extracted mainly by socio-economic challenges and weak institutional responses. The study suggests legal harmonisation, improved cross-border information exchange, more comprehensive policies to address human trafficking in Kosovo, enhanced victim protection services, and advanced digital tools for investigation purposes. These insights have implications for criminal justice scholars and policy-makers focused on human rights. The paper provides a unique contribution by presenting recent empirical data on human trafficking and offering insights into the current situation, highlighting urgent areas of policy reform and making it a valuable resource for academics and policy-makers.